Mechanical characterization and visco-hyperelastic modeling of epithelial cells: Pressure-rate dependency of the apparent elastic modulus - Garcia-Herrera, C (Elsevier Ltd, 2026)
In this study, an experimental and numerical characterization of the viscohyperelastic behavior of suspended epithelial ARPE-19 cells is carried out using the micropipette aspiration technique, with particular emphasis on the evaluation of two viscoelastic models with different mathematical formulations, which were implemented in an in-house finite element code. The tests, conducted under one and two-ramp aspiration protocols, revealed variations in the measured mechanical properties of the cells, which are first sensitive to the applied pressure levels; This dependency is attributed to the internal organization of subcellular components. Second, the aspiration tests show that the apparent elastic modulus is dependent to the applied pressure rate. Two visco-hyperelastic models were evaluated to replicate the experimentally observed behavior. Although both models successfully fit the results, the LM model proved to be more efficient, requiring fewer parameters and enabling a clearer physical interpretation of the viscoelastic properties. In the numerical calculations, a time- and geometry-dependent load function was implemented, which optimally replicated the experimental observations while maintaining low computational cost. © 2025 Elsevier Ltd.